Identification of highly expressed genes and efficient core promoters specific to buffalo skeletal muscles - J. Huang; J. Huang; D. Guo; R. Zhu; H. Wang; C. Yang; D. Shi; J. Shang (Archives Animal Breeding)
An efficient promoter with specific transcriptional activity plays significant roles in the regulation of expression of exogenous genes. The efficient promoter specific to skeletal muscles can achieve high expression of exogenous genes in skeletal muscles. This is of great significance for the targeted improvement of livestock meat quality by combining gene editing and traditional breeding techniques. To identify efficient promoters specific to the skeletal muscles of buffalo, in the present study, a total of 14 genes, CACNG1, LRRC30, CACNG6, MYOG, VGLL2, MYOD1, KCNA7, DUPD1, PRR32, LBX1, IGFN1, ACTN3, PITX3, and MURC, were firstly screened as skeletal-muscle-specific expressed genes based on high-throughput sequencing data. Among them, only two genes – namely, VGLL2 and CACNG1 – were identified to be specifically and efficiently expressed in the skeletal muscles of buffalo by quantitative reverse transcription polymerase chain reaction (RT-qPCR). Then, the transcriptional activity of different truncated fragments of the upstream putative promoter region of VGLL2 and CACNG1 were evaluated by the dual luciferase reporter gene detection system in mouse C2C12 cells and buffalo skeletal muscle cells. As a result, both core promoters of VGLL2 and CACNG1 were identified to have specifically and efficiently transcriptional activity in skeletal muscle tissue while the transcriptional activity of the core promoters of VGLL2 was more efficient. These results provide significant information for the targeted improvement of meat quality in buffaloes and other livestock animals.